Geloven in een democratie?: Over religie en publiek domein - Wilgenburg, Arwin van (Tijdschrift voor theologie, 2011)
Starting from the perspective of public theology, this article treats the question of philosophical multiformity in a democracy. Democracy risks becoming dispirited by unbridled individualism and the related lack of social participation. This article argues that the Christian faith can offer a constructive contribution to the concern it shares with humanism for the humane in the political. To do this, Christianity would have to take a serious look at humanism’s criticism that religion sows division and is even potentially violent. Responding to P. Cliteur’s book on Het monotheïstisch dilemma: Of: de theologie van het terrorisme [The Monotheist Dilemma: Or: The Theology of Terrorism] (2010), this article discusses his assertion that a neutral state and an autonomous ethic should be the answer to the potential for violence in monotheistic religions. According to Cliteur, proponents of a monotheistic religion in a democracy have a dual citizenship: they obey the laws of the constitutional state in which they live and they obey commandments founded on religion. This dilemma can culminate in religious terrorism. For this reason, Cliteur argues for a secular monotheism. While Cliteur sees no promise in hermeneutical theology (since it purportedly is unable to take the problem of religious violence seriously), the article argues that this path does offer a fruitful perspective for the problem of religious violence. Monotheism is more concerned with criticism of faith than about the faith criticised (M. De Kesel). The monotheist dilemma should not be resolved from this perspective because it lies at the heart of religious criticism that unmasks every religious claim to act in God’s name. In the hermeneutic tradition, God and mankind are not competitors. Hermeneutic rationality liberates the notion of God from the instrumental thinking within which God can only be imagined in terms of directing and dominating. From this perspective, Christians can fully underwrite the universal declaration of human rights. At the same time, we can build a bridge to humanist philosophers like F. Savater and L. Ferry who offer their critique on the monopoly of instrumental reason, from a secular perspective. Instead of looking upon philosophical diversity as a threat, believers and non-believers should believe fully in democracy as the pursuit of a truly worthy society for all. One of public theology’s tasks is to help implement civic responsibility understood as humaneness, by questioning modern views of humanity, by finding ways to build non-exclusive communities, by exploring what we consider holy and what drives us and by developing a theology of peace that presupposes ecumenical discussions and inter-religious dialogue as well as bridges the gap between church and world.